Changes in the expression of GABAA receptor subunit mRNAs in parahippocampal areas after kainic acid induced seizures - Drexel, Meinrad; Kirchmair, Elke; Sperk, Gunther (Frontiers in Neural Circuits, 2013)
The parahippocampal areas including the subiculum, pre- and parasubiculum and notably the entorhinal cortex are intimately involved in the generation of limbic seizures in temporal lobe epilepsy. We investigated changes in the expression of 10 major GABAA receptor subunit mRNAs in subfields of the ventral hippocampus, ventral subiculum, entorhinal cortex and perirhinal cortex at different intervals (one, 8, 30 and 90 days) after kainic acid (KA)-induced status epilepticus priming epileptogenesis in the rat. The most pronounced and ubiquitous changes were a transient (24 hrs after KA only) down-regulation of γ2 mRNA and lasting decreases in subunit α5, β3 and δ mRNAs that were prominent in all hippocampal and parahippocampal areas. In the subiculum similarly as in sectors CA1 and CA3, levels of subunit α1, α2, α4, and γ2 mRNAs decreased transiently (one day after KA-induced status epilepticus). They were followed by increased expression of subunit α1 and α3 mRNAs in the dentate gyryrus and sectors CA1 and CA3, and subunit α1 also in the entorhinal cortex layer II (30 and 90 days after KA). We also observed sustained overexpression of subunits α4 and γ2 in the subiculum and in the Ammon’s horn. Subunit γ2 mRNA was also increased in sector CA1 at the late intervals after KA. Taken together, our results suggest distinct regulation of mRNA expression for individual GABAA receptor subunits. Especially striking was the wide-spread down-regulation of the often peri- or extra-synaptically located subunits α5 and δ. These subunits are often associated with tonic inhibition. Their decrease could be related to decreased tonic inhibition or may merely reflect compensatory changes. In contrast, expression of subunit α4 that may also also tonic inhibition when associated with the δ subunit was significantly up-regulated in the dentate gyrus and in the proximal subiculum at late intervals. Thus, concomitant up-regulation of subunit γ2 and α1, α4 mRNAs (and loss in δ subunits) ul